Carboranethiol-Protected Propeller-Shaped Photoresponsive Silver Nanomolecule - Jana, Arijit; Unnikrishnan, Parvathy M; Poonia, Ajay K; Roy, Jayoti; Jash, Madhuri; Paramasivam, Ganesan; Machacek, Jan; Adarsh, Kumaran Nair Valsala Devi; Base, Tomas; Pradeep, Thalappil (Inorganic chemistry, 2022)
We report the synthesis, structural characterization, and photophysical properties of a propeller-shaped Ag21 nanomolecule with six rotary arms, protected with m-carborane-9-thiol (MCT) and triphenylphosphine (TPP) ligands. Structural analysis reveals that the nanomolecule has an Ag13 central icosahedral core with six directly connected silver atoms and two more silver atoms connected through three Ag-S-Ag bridging motifs. While 12 MCT ligands protect the core through metal-thiolate bonds in a 3-6-3-layered fashion, two TPP ligands solely protect the two bridging silver atoms. Interestingly, the rotational orientation of a silver sulfide staple motif is opposite to the orientation of carborane ligands, resembling the existence of a bidirectional rotational orientation in the nanomolecule. Careful analysis reveals that the orientation of carborane ligands on the cluster's surface resembles an assembly of double rotors. The zero circular dichroism signal indicates its achiral nature in solution. There are multiple absorption peaks in its UV-vis absorption spectrum, characteristic of a quantized electronic structure. The spectrum appears as a fingerprint for the cluster. High-resolution electrospray ionization mass spectrometry proves the structure and composition of the nanocluster in solution, and systematic fragmentation of the molecular ion starts with the loss of surface-bound ligands with increasing collision energy. Its multiple optical absorption features are in good agreement with the theoretically calculated spectrum. The cluster shows a narrow near-IR emission at 814 nm. The Ag21 nanomolecule is thermally stable at ambient conditions up to 100 °C. However, white-light illumination (lamp power = 120-160 W) shows photosensitivity, and this induces structural distortion, as confirmed by changes in the Raman and electronic absorption spectra. Femtosecond and nanosecond transient absorption studies reveal an exceptionally stable excited state having a lifetime of 3.26 ± 0.02 μs for the carriers, spread over a broad wavelength region of 520-650 nm. The formation of core-centered long-lived carriers in the excited state is responsible for the observed light-activated structural distortion.